Peranan Strategis Mangrove Mulai dari Konservasi, Ekonomi, dan Pemberdayaan Masyarakat yang Berada di KTH Salo Sumbala, Muara Badak Ulu, Kabupaten Kutai Kartanegara, Kalimantan Timur - Aufri Najwan Fazari; Alzahra Zharifa Erwanda; Muhammad Ahyar Ma’ali; Nini Marlina; Aisyah Tri Andhini; Shafa Salsabila; Maria Aurelia Olivera Bedhi; Muhammad Tezar; Aulia Safrina; Nisrina Salsabila Zahra; Akbar Lufi Zulfikar (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Mangroves play a crucial strategic role in maintaining coastal ecosystem balance, serving as habitats for aquatic organisms and functioning as natural biofilters that help reduce pollution. Nevertheless, mangrove degradation in Indonesia, including in Kutai Kartanegara Regency, remains a significant challenge caused by human activities such as aquaculture expansion, settlement growth, and industrial development. Muara Badak Ulu Village, located within this regency, possesses extensive mangrove resources that require integrated conservation strategies. This community service program was carried out in collaboration with the Salo Sumbala Forest Farmers Group (KTH) to promote conservation, sustainable economic development, and local community empowerment. The activities included the installation of educational banners, community-based mangrove replanting, and the production of a profile video highlighting local potential. Over a 40-day period, these initiatives received enthusiastic responses from local residents, reflecting increased awareness of the ecological and economic importance of mangroves. The program emphasized participatory approaches, where local community members, particularly KTH, were actively engaged in every stage of planning and implementation. Beyond ecological benefits, the initiative is expected to support sustainable management of non-timber forest products, enhance economic opportunities, and strengthen environmental stewardship among coastal communities. Overall, this program demonstrates that community-driven mangrove conservation can generate multiple impacts: restoring degraded ecosystems, fostering collective awareness, and building resilience in coastal areas facing environmental challenges. Thus, the collaboration between higher education institutions and local communities provides a practical model for achieving sustainable development and environmental preservation.